2006
DOI: 10.1002/uog.2692
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound imaging of the lower urinary tract after successful tension‐free vaginal tape (TVT) procedure

Abstract: Objectives To evaluate changes in the mobility of the whole urethra, in the proximal urethra (funneling)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 31 publications
3
18
0
3
Order By: Relevance
“…At maximum retaining, the angle closes through the traction of the two arms, probably due to reduced distension, with the levator plate raising the anterior vaginal wall. These tapes work as a dynamic closing mechanism which affects the urethra as intraabdominal pressure is increased (Valsalva and maximum retaining): the urethra and surrounding tissue are also compressed against the tape [18].…”
Section: Discussionmentioning
confidence: 99%
“…At maximum retaining, the angle closes through the traction of the two arms, probably due to reduced distension, with the levator plate raising the anterior vaginal wall. These tapes work as a dynamic closing mechanism which affects the urethra as intraabdominal pressure is increased (Valsalva and maximum retaining): the urethra and surrounding tissue are also compressed against the tape [18].…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that ES is a simple, fast and non-invasive imaging technique in the diagnosis of SUI (24) . Tissue The utility of elastosonography for assessing suburethral tissue elasticity in women with stress urinary incontinence…”
Section: Discussionmentioning
confidence: 64%
“…This is the reason why it is nowadays used in urogynecologic patients more often [17,23,24]. The urethral mobility assessment performed with transperineal 2D ultrasound imaging with a transabdominal probe confirmed good reproducibility of similar measurements [15,16,25,26]. A comparison of three different methods of measuring urethrovesical mobility showed that the Q-tip test and the Sensor-Q had higher inter-observer reliability of urethral mobility evaluation than the ultrasound method [22].…”
Section: Discussionmentioning
confidence: 98%